PI control for a continuous fermentation process with a delayed product inhibition. (December 2018) - Skupin, Piotr; Metzger, Mieczyslaw
Highlights: A continuous fermentation process with a delayed product inhibition is considered. Stability analysis of the control system with PI algorithm and process delay is given. The negative effect of measurement noises is considered. The process is stabilized for any delay and for a sufficiently high controller gain. Filtering of the process variable reduces the effect of noises, but affects stability. Abstract: The paper addresses the problem of stabilization of ethanol concentration in continuous fermentation processes. The stability analysis is performed for a class of continuous fermentation processes assuming that the possible oscillatory behavior results from a delayed response of microorganisms to inhibitory effects of ethanol concentration and that the specific growth rate is a monotonic function of substrate and a monotonic function of product concentrations. Treating dilution rate as the manipulated variable, it is shown that the classical PI controller is able to stabilize the oscillating process in the whole range of operating regions. Moreover, for a sufficiently large controller gain, the closed-loop system is asymptotically stable for any process delay. However, a high-gain controller may lead to extensive control signal activity and wear of actuator in the presence of measurement noises. To reduce the negative effect of measurement noises, the measured process variable is filtered by using the first order filter. Then, it is shown that the closed-loop system with the filter can also be stabilized for any process delay. The simulation results confirmed the effectiveness of the proposed closed-loop strategy with and without filtering.